2014
DOI: 10.17645/si.v2i2.166
|View full text |Cite
|
Sign up to set email alerts
|

Antisemitism and Jewish Children and Youth in Australia’s Capital Territory Schools

Abstract: Issues pertaining to religion and Australian schools have generated a significant amount of controversy and scholarly attention in recent years, and much of the attention in the religion and schools debate has focused on Muslim and nonreligious children's experiences (Erebus International, 2006;Halafoff, 2013). This article, by contrast, explores the manifestations of antisemitism as experienced by Jewish children and youth in Canberra schools. It considers the characteristics of antisemitism; when and why it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In addition to the findings from research conducted in the UK, since 2010 there has been a small body of empirical research across a number of other countries, including Australia (Ben-Moshe & Halafoff, 2014; Gross & Rutland, 2014), Norway (Thomas, 2016), Sweden (Bevelander & Hjern, 2015), and the USA (Dupper, Forrest-Bank, & Lowry-Carusillo, 2015;Forrest & Dupper, 2016) which either investigates the attitudes of young people towards their Jewish peers (Villano, 1999;Bevelander & Hjerm, 2015;Thomas, 2016), or which explores directly the lived experience of hostility, stereotyping and prejudice as encountered and reported by Jewish young people in schools (Ben-Moshe & Halafoff, 2014;Gross & Rutland, 2014;Dupper, Forrest-Bank, & Lowry-Carusillo, 2015).…”
Section: Anti-semitismmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the findings from research conducted in the UK, since 2010 there has been a small body of empirical research across a number of other countries, including Australia (Ben-Moshe & Halafoff, 2014; Gross & Rutland, 2014), Norway (Thomas, 2016), Sweden (Bevelander & Hjern, 2015), and the USA (Dupper, Forrest-Bank, & Lowry-Carusillo, 2015;Forrest & Dupper, 2016) which either investigates the attitudes of young people towards their Jewish peers (Villano, 1999;Bevelander & Hjerm, 2015;Thomas, 2016), or which explores directly the lived experience of hostility, stereotyping and prejudice as encountered and reported by Jewish young people in schools (Ben-Moshe & Halafoff, 2014;Gross & Rutland, 2014;Dupper, Forrest-Bank, & Lowry-Carusillo, 2015).…”
Section: Anti-semitismmentioning
confidence: 99%
“…The negativity shown toward their faith and experienced by Jewish students in studies both in the UK and internationally was not always to the exclusion of more positive interactions with peers. Both Moulin (2016, p. 692) and Ben-Moshe and Halafoff (2014) reported Jewish students also describing relationships characterised by more positive intergroup contact in that they also had non-Jewish friends who rejected anti-Semitism, and who included them in their friendship groups. Ben-Moshe and Halafoff (2014, p. 53) concluded that the social inclusion and social exclusion of Jewish students was 'occurring simultaneously.…”
Section: Anti-semitismmentioning
confidence: 99%